JORGE LUIS BORGES'S CREATIVE WRITINGS IN THE CONTEXT OF LANGUAGE CULTURE - Navarenko, Inna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of the work of H. L. Borges in the context of the culture of speech. The paper analyzes ways of conceptualizing reality, the formation and representation of knowledge about the world in the context of national identity, as well as the way people perceive the world through language. Formulated setting to explore the language in close connection with the thinking, consciousness, cognition, culture, worldview as an individual and the language team to which he belongs.The special interest of modern cognitive linguistics to the definition of linguistic identity as a set of mechanisms for generating, understanding and storing it in the national consciousness, that is, disclosing the mechanisms of national culture and the culture of an individual, characterizing the general process of human language activity, is defined.The role of linguistic consciousness is highlighted, by which one understands the subject’s knowledge of the world and oneself.Research interest is the work of Argentine writer and thinker Jorge Luis Borges, who raises the problem of the existence of Latin American culture in general and at the same time feels like the heir to all cultures of the American continent, without diminishing the role of Argentines in world culture.Borges prose is a world of metaphorical symbols that he created in his works in the form of library labyrinths, where the main textual relationships are: nature – culture, God – man, knowledge – faith, book – language, Library – Universe. Imagination in the understanding of Borges is not only a means of functioning of the creative process, but also as a source of inspiration and support in human life, and the letter, word, book – these are the code keys through which a person knows the world.____________ReferencesVezhbickaja, A. Semanticheskie universalii i opisanie jazyka (Moskva, 1999): 293.Karasik, V. I. «O kategorijah lingvokul'turologii.» Jazykovaja lichnost': problemy kommunikativnoj dejatel'nosti (Volgograd, 2001): 3-16.Gnatjuk, P. P. «Movna svidomist' u suchasnij lingvistychnij paradygmi.» Ukrai'ns'ke movoznavstvo 34 (2005): 3-8.Ejger, G. V. Mehanizmy kontrolja jazykovoj pravil'nosti vyskazyvanija (Har'kov, Osnova, 1990), 184.Dzhozef, Dzh., dostup http://www.nasonline.org/Borges, J. L. La biblioteca de Babel, Ficciones. Obras Completas (Buenos Aires, EMECE, 1985), 465.Borges, J. L. Abenjacán el Bojarí, muerto en su laberinto (El Aleph. op. cit.), 601.Borges, J. L. El jardín de senderos que se bifurcan, Ficciones (Quinta edición, 2013), 221.Borges, J. L. La muerte y la brújula, Ficciones (Quinta edición, 2013), 221.
Keywords: cognitive linguistics, conceptualization of reality, culture of speech, metaphorical symbol, language consciousness, national culture, national consciousness, worldview